Physical fitness testing in youth soccer: Issues and considerations regarding reliability, validity, and sensitivity - Paul, D. J.; Nassis, G. P. (Pediatric Exercise Science, 2015)
The importance of physical fitness testing in youth soccer players has become more evident over recent years.